Water parameters and primary productivity at four marine embayments of Costa Rica (2000-2002) - Vargas-Zamora, José A.; Acuña-González, Jenaro; Sibaja-Cordero, Jeffrey A.; Gómez-Ramírez, Eddy H.; Agüero-Alfaro, Grettel; García-Céspedes, Jairo (Revista de Biología Tropical, 2018)
Abstract: The availability of baseline data on water parameters and primary productivity is essential in comparative studies aimed at identifying environmental trends, like eutrophication, in coastal embayments. In this context, the objetive of this work is to make accessible data, collected from 2000 to 2002, on 13 water parameters (Secchi depth, temperature, salinity, dissolved oxygen, oxygen saturation, suspended matter, chlorophyll-a, phaeopigments, phosphate, silicate, ammonium, nitrite and nitrate) their temporal and spatial distribution, and primary productivity at four coastal sites of Costa Rica. The multi-parameter survey was conducted based on surface (1 m deep) water samples collected at a total of 128 stations at three Pacific and one Caribbean embayments: a bay under the influence of upwelling (Culebra Bay), a tidal estuary (Gulf of Nicoya), a semi-enclosed small coastal bay bordered by mangroves (Golfito Bay), and a Caribbean bay and port (Moin Bay). Graphic distributions of stations from the four embayments and for the Gulf of Nicoya were obtained by Principal Component Analysis (PCA).PCA Gabriel biplots were used to illustrate the relative importance of each parameter on the separation of stations. The four embayments were separated by PCA based on the 13 parameters. The maximum values recorded were: Secchi depth: 12.6 m; salinity: 35 psu; temperature: 32.5 oC; oxygen: 11.4 mg/L; oxygen saturation: 188 %; suspended matter: 156.04 mg/L; chlorophyll-a: 16.21 mg/m3; phaeopigments: 6.37 mg/m3; phosphate: 9.53 µmol/L; silicate: 156.11 µmol/L; ammonium: 2.66 µmol/L; nitrite: 2.47 µmol/L; and nitrate: 4.59 µmol/L. Salinity and several nutrients varied seasonally (dry vs rainy) in the Gulf of Nicoya estuary. Estimates of net primary productivity (Winkler oxygen method) produced a maximum 2 206 g C/m2/year at Culebra Bay. The maximum net PP (g C/m2/year) at the other three embayments, were: 1 601 (Gulf of Nicoya), 1 371 (Golfito Bay), and 1 100 (Moín Bay). Net PP values showed high variability in space and time, and ranged from negative to those associated with oligotrophic, eutrophic, and hypertrophic waters. In the Gulf of Nicoya 60 % of the values of net PP exceeded the reference value (500 g C/m2/year) to separate eutrophic from hypertrophic conditions. Rev. Biol. Trop. 66(Suppl. 1): S211-S230. Epub 2018 April 01.